‘Preaching of’ and ‘Believing in’ Jesus in the 4th and 5th Centuries: Nicetas of Remesiana (ca. 335‐414) - Bianco, Maria Grazia (Vox Patrum, 2025)
Niceta (ca. 335-after 414) was a bishop of Remesiana (Serbia) who traveled by land to proclaim the Gospel. Although he is the only witness to Latin culture in the Danuban area between the 4th and 5th century, still he is an author very little studied; the fragments of his catechesis attest to the liveliness and richness of the language of an educated person, committed to pastoral work and capable of immediate contact with his listeners. The most important work of Niceta is Instructiones. It is a simple, clear exposition of the Christian doctrine, almost a western complement to the catechesis of the Greek theologian Cyril. Niceta shows a kind of instinctive reluctance towards the tortuous arguments on the Trinitarian debate. He shows himself interested in spiritual theology and attentive to an exposition of the Christian message accessible to all. In this paper I will present two examples of the proclamation of Jesus on the early 5th century: the first one referring to Augustine’s De catechizandis rudibus, and the second to Niceta’s works. There is a difference between these two authors: Augustine illustrates how to catechize those who have already decided to receive the baptism, while Niceta addresses people who do not know Jesus at all. In the 8th century Niceta’s works have been suggested by Alcuin to Arno of Salzburg to catechize peoples conquered by Charlemagne.